UPSUS PAJALE DALAM MENUNJANG PROGRAM SWASEMBADA PANGAN DI KABUPATEN BOLAANG MONGONDOW - Jeremy ., Ponto; Noortje M. Benu; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the trend of agricultural production in supporting food self-sufficiency program "PAJALE" in Bolaang Mongondow District. This research conducted for 3 months. The data used in this research is secondary data obtained from Agriculture Department of North Sulawesi Province. The variables that will be measured in this research are (1). Rice production Year 2015 - 2016, (2). Corn production Year 2015 - 2016, (3). Soybean Production Year 2015 - 2016. The analysis used in this research is descriptive analysis using time series data. In conclusion, the production of rice, corn and soybean crops in 2015 is ATAP 2015 data. The research shows that there is an increase in rice production, corn, soybean in Bolaang Mongondow in 2015 - 2016, due to the presence of UPSUS in the form of 2015 until 2017.